Pharmacokinetics effects of chuanxiong rhizoma on warfarin in pseudo germ-free rats - Li, Haigang; Zhou, Yi; Liao, Luanfeng; Tan, Hongyi; Li, Yejun; Li, Zibo; Zhou, Bilan; Bao, Meihua; He, Binsheng (Frontiers in Pharmacology, 2023)
Aim: In China, warfarin is usually prescribed with Chuanxiong Rhizoma for treating thromboembolism diseases. However, the reason for their combination is still being determined. The present study explored the pharmacokinetics interactions of warfarin, Chuanxiong Rhizoma, and gut microbiota in the rat model of middle cerebral artery occlusion (MCAO). Methods: A total of 48 rats were randomly divided into six groups: MCAO rats orally administered warfarin (W group), pseudo germ-free MCAO rats orally administered warfarin (W-f group), MCAO rats co-administered Chuanxiong Rhizoma and warfarin (C+W group), pseudo germ-free MCAO rats co-administered Chuanxiong Rhizoma and warfarin (C+W-f group), MCAO rats co-administered warfarin and senkyunolide I (S+W group); pseudo germ-free MCAO rats co-administered warfarin and senkyunolide I (S+W-f group). After treatment, all animals' blood and stool samples were collected at different time points. The stool samples were used for 16S rRNA sequencing analysis. Ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) method was established to quantify warfarin, internal standards, and the main bioactive components of Chuanxiong in blood samples. The main pharmacokinetics parameters of warfarin were calculated by DAS 2.1.1 software. Results: The relative abundance of Allobaculum and Dubosiella in the pseudo germ-free groups (W-f, C+W-f, S+W-f) was lower than that in the other three groups (W, C+W, S+W). The relative abundance of Lactobacillus in the W-f group was higher than that of the W group, while the relative abundance of Akkermansia decreased. The relative abundance of Ruminococcaceae_UCG-014 and Ruminococcaceae_NK4A214_group in the S+W-f group was lower than in the S+W group. Compared to the W group, the AUC0-t and Cmax of warfarin in the W-f group increased significantly to 51.26% and 34.58%, respectively. The AUC0-t and Cmax in the C+W group promoted 71.20% and 65.75% more than the W group. Compared to the W group, the AUC0-t and Cmax obviously increased to 64.98% and 64.39% in the S+W group. Conclusion: Chuanxiong Rhizoma and senkyunolide I (the most abundant metabolites of Chuanxiong Rhizoma aqueous extract) might affect the pharmacokinetics features of warfarin in MCAO rats through, at least partly, gut microbiota.